2021
DOI: 10.1101/2021.06.30.21259757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Impact of Sociocultural Gender on Post-acute Sequelae of COVID-19: a Bayesian Approach

Abstract: Background: Evidence to date indicates that mortality of acute coronavirus disease (COVID-19) is higher in men than in women. Conversely, women seem more likely to suffer from long-term consequences of the disease and pronounced negative social and economic impacts. Sex- and gender-specific risk factors of COVID-19-related long-term effects are unknown. Methods: We conducted a multicentre prospective observational cohort study of 5838 (44.6% women) individuals in Switzerland who were tested positive for SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 69 publications
2
27
0
3
Order By: Relevance
“…In our study, we find the expected direction of effect; however, it is overall a small effect. Possibly, with increasing knowledge on the shortand long-term health risks, such as long COVID [33,34], and the personal inconveniences resulting from a suspected or true infection, such as isolation or quarantine, the perception of risk has changed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we find the expected direction of effect; however, it is overall a small effect. Possibly, with increasing knowledge on the shortand long-term health risks, such as long COVID [33,34], and the personal inconveniences resulting from a suspected or true infection, such as isolation or quarantine, the perception of risk has changed.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance in particular of fatigue and neurocognitive impairment is noteworthy for three reasons. First, fatigue or tiredness and exercise intolerance and similar problems are definitely more frequent in COVID-19 survivors than in control populations [14][15][16][17][18][19][20] and have been the main complaints in many long covid studies, but few of them (12 of 43 evaluable studies in a recent review) used standardised instruments to quantify or validate self-reported symptoms of fatigue. 9 The FAS instrument used by us and in a population-based Swiss study 15 assesses fatigue largely distinct from depressive symptoms, anxiety, and neuroticism, and seemed to support the validity of self-reported symptoms of fatigue with different grades of impairment in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, for MPA significantly higher levels could be seen than in fully vaccinated individuals. Thinking of highly prevalent symptoms of post-COVID-19 syndrome 34,35 such as exercise intolerance and reduced resilience or simply the deconditioning experienced after a period of bed rest, these individuals might be dedicated to getting back in shape or counteracting residual symptoms. The abovementioned findings, taken together, highlight the role of vaccination status as an explanatory variable for changes in PA patterns in the current situation.…”
Section: Association Between Vaccination Status and Pa Patternsmentioning
confidence: 99%
“…The latter two barriers are in line with data on post-COVID-19 syndrome. 34,35 However, the lack of evidence may be explained by the circumstances the survey was conducted inlow occurrence of infections, mild safety measures, and for instance in Switzerland no vaccination certificate mandate at the time. 38…”
Section: Association Between Vaccination Status and Barriers To Pamentioning
confidence: 99%